2011
DOI: 10.1111/j.1443-1661.2010.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sphincterotomy Plus Endoprostheses in the Treatment of Large or Multiple Common Bile Duct Stones

Abstract: Biliary plastic stents plus endoscopic sphincterotomy without stone extraction as primary therapy at initial ERCP is a safe and effective method in the management of large or multiple CBD stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 20 publications
5
50
0
Order By: Relevance
“…Indeed, no stones were detected in one patient in each group at the second ERCP. Other studies also showed similar results (16,20,22).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Indeed, no stones were detected in one patient in each group at the second ERCP. Other studies also showed similar results (16,20,22).…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, we considered that the results might be only slightly affected by stent migration. It is postulated that movements of the stone in the dilated duct promote the extrusion of the stent into the duodenum (22,25). The optimal type of stent has not yet been ascertained, although previous studies demonstrated that a pigtail stent may provide a lower risk of migration, cholangitis and perforation (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, stent placement may [15]. No evidence of stones was seen in many cases during the second ERCP performed after several months, meaning that spontaneous passage of stones from the bile duct has occurred [14,16]. In this study, the second ERCP revealed that 23 % of stented patients had spontaneous stone passage.…”
Section: Discussionmentioning
confidence: 71%